Mechanics of flight in ski jumping: aerodynamic stability in roll and yaw - Marques-Bruna, P.; Grimshaw, P. (Sports Technology, 2009)
This study identifies the mechanisms of static and dynamic, lateral and directional aerodynamic stability in ski jumping based upon theoretical principles of aerodynamics and aeronautics. Static stability for systematic variations in flight posture was simulated utilizing an inertia model of the ski jumper generated using computer-aided design and mathematical modeling. Theory suggests that differential ski velocity and asymmetric angle of attack provide aerodynamic damping during a roll. Ski dihedral and lateral centre-of-pressure migration produce a restorative dihedral effect. However, forward sweep, body-ski interaction and ski side drag are destabilizing in roll. Differential ski tangential velocity provides aerodynamic damping during yawing motion; however, forward sweep, slender-body flow and body-ski interaction are destabilizing in yaw. Only the ski-shielding effect contributes to static yaw stability. Rolling and yawing motion impinge upon one another. Aerodynamic damping of dynamic Dutch roll oscillation is only light, however inertial damping of dynamic oscillation is heavy in ski jumping. The simulation data suggest that a flight posture of a ski opening angle of 30° and forward leaning angle of 10° enhances inertial damping and aerodynamic stability at any competition level. This theoretical analysis lays the foundations for the wind tunnel-based study of integrated flight stability, where it is imperative to determine the influence of real viscous effects upon flight stability. The present analysis has also applications for enhanced safety in ski jumping.